Fish cage culture in small water bodies in North East Region of Ghana: technical and institutional guiding principles for sustainable and inclusive uptake - Buisson, Marie-Charlotte; Zane, Giulia; Appiah, Sarah; Mapedza, Everisto D.; Asmah, R.; Ahiah, L. A.; Mensah, E. T. D. (International Water Management Institute, 2023)
The CGIAR Initiative on Aquatic Foods partnered with the Council for Scientific and Industrial Research’s Water Research Institute (CSIR-WRI), the Fisheries Commission, and collaborated with local government departments and local communities to implement fish cage culture in selected small reservoirs in Ghana. This brief highlights the technical and institutional principles that were applied in these sites for inclusive and sustainable aquatic food production in the year 2023.